Profiling visitors and selection of appropriate events to attract visitors to Zoo Negara / Nurul Hafida Safarina Abd Karim - Abd Karim, Nurul Hafida Safarina (Faculty of Business and Management, 2007)
This research is about profiling visitors and selection of appropriate events to attract visitors at Zoo Negara. Factors such as types of event, event characteristics and past experience have been identified in order to investigate whether or not these factors have a relationship with intended frequency of visits. To serve the purpose, a descriptive research is carried out to obtain result about visitors profiling and the event attractiveness. The survey is conducted at main entrance Zoo Negara, Hulu Kelang Selangor. The sample size for this study is 80 visitors from Zoo Negara. Data obtained using two methods that are primary and secondary data. Respondents are required to answer the questionnaires that contain element that potentially have relationship with event management. Data are analyzed using Reliability Test, Pearson Correlation Analysis as well as Gap analysis through SPSS Program. In the findings, it shows that most of the respondents are not satisfied with the services given by Zoo Negara. Most of the respondents are not satisfied with the restaurant with perceived (mean) > expected (mean) with the gap of -0.25. The respondents are very satisfied with train services with mean gap of 0.12. Also, the research findings show that there a two factors of events that have association between intended frequencies of visit. The two factors are events characteristics and past history. By recognizing the problem and the consequences of the event attractiveness, it will be then providing a general guideline to improve the Zoo Negara services and event management. The recommendations and suggestions on how to attract visitors especially through events have been identified.